Emotional vs. Informational Content: Analyzing Their Impact on Audience Engagement in Instagram Marketing for Local Sportswear Brands in Indonesia - Muhammad Maula Razak (Hasanuddin Economics and Business Review, 2026)
This study aims to analyze the influence of content type emotional versus informational on the engagement level of Instagram posts by local sportswear brands in Indonesia. This research employs a quantitative approach with an explanatory research design. Data was collected through web scraping of Instagram posts from five local sportswear brands. The final sample consists of 330 posts, which were analyzed using multiple linear regression (OLS). Engagement is measured by an aggregate index based on the number of likes and comments, transformed logarithmically, and re-tested with alternative indicators. The model also controls for post characteristics, content format, posting time, and brand differences. The results show that emotional content has a positive and significant relationship with overall engagement, particularly in driving likes. However, this effect was not significant for comments. The video format did not increase overall engagement or moderate the effect of content type but positively influenced comments, representing a more intensive form of engagement. This study concludes that Instagram content effectiveness is contextual and multidimensional. Emotional content is more effective in triggering immediate responses, while deeper engagement is influenced by a combination of factors beyond message orientation alone. These findings contribute empirically to digital marketing literature and provide practical implications for content strategy in local sportswear brands.